2004
DOI: 10.1124/mol.65.5.1159
|View full text |Cite
|
Sign up to set email alerts
|

Activators of the Rat Pregnane X Receptor Differentially Modulate Hepatic and Intestinal Gene Expression

Abstract: Ligand-mediated activation of the pregnane X receptor (PXR, NR1I2) is postulated to affect both hepatic and intestinal gene expression, because of the presence of this nuclear receptor in these important drug metabolizing organs; as such, activation of this receptor may elicit the coordinated regulation of PXR target genes in both tissues. Induction of hepatic and intestinal drug metabolism can contribute to the increased metabolism of drugs, and can result in adverse or undesirable drug-drugis a potent activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
66
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 40 publications
3
66
0
Order By: Relevance
“…9). PXR ligands have been reported to induce the expression of Sult1a1 in female rats (Hartley et al, 2004), male rats (Liu and Klaassen, 1996;Rushmore and Kong, 2002), 1b1 in female rats (Hartley et al, 2004); 1d1 and 1e1 in male mice (Sonoda et al, 2002); 2a1 in male rats (Liu and Klaassen, 1996;Runge-Morris et al, 1996;Rushmore and Kong, 2002), male mice (Sonoda et al, 2002;Echchgadda et al, 2004a;Kim et al, 2004), female mice (Sonoda et al, 2002), and human hepatocytes (Duanmu et al, 2002); and PAPSs2 in male mice (Sonoda et al, 2002). In contrast, PXR ligands were reported to have no influence on the expression of Sult1a1 in male mice (Maglich et al, 2002), human hepatocytes (Duanmu et al, 2002), male rats (Liu and Klaassen, 1996;Duanmu et al, 2001), and female rats (Liu and Klaassen, 1996); 1c1 in male and female rats (Liu and Klaassen, 1996); 1d1 in male mice (Maglich et al, 2002); 1e1 in male and female rats (Liu and Klaassen, 1996); 2a1 in mice (Saini et al, 2004), and male and female rats (Liu and Klaassen, 1996); and 2b1 in male mice (Maglich et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…9). PXR ligands have been reported to induce the expression of Sult1a1 in female rats (Hartley et al, 2004), male rats (Liu and Klaassen, 1996;Rushmore and Kong, 2002), 1b1 in female rats (Hartley et al, 2004); 1d1 and 1e1 in male mice (Sonoda et al, 2002); 2a1 in male rats (Liu and Klaassen, 1996;Runge-Morris et al, 1996;Rushmore and Kong, 2002), male mice (Sonoda et al, 2002;Echchgadda et al, 2004a;Kim et al, 2004), female mice (Sonoda et al, 2002), and human hepatocytes (Duanmu et al, 2002); and PAPSs2 in male mice (Sonoda et al, 2002). In contrast, PXR ligands were reported to have no influence on the expression of Sult1a1 in male mice (Maglich et al, 2002), human hepatocytes (Duanmu et al, 2002), male rats (Liu and Klaassen, 1996;Duanmu et al, 2001), and female rats (Liu and Klaassen, 1996); 1c1 in male and female rats (Liu and Klaassen, 1996); 1d1 in male mice (Maglich et al, 2002); 1e1 in male and female rats (Liu and Klaassen, 1996); 2a1 in mice (Saini et al, 2004), and male and female rats (Liu and Klaassen, 1996); and 2b1 in male mice (Maglich et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The differential activation of target genes, is most probably reflective of the differential coregulator pool present in each tissue, and reflects the most efficient response to chemical challenge. For example, previous experiments demonstrated that CYP3A was induced in both rat liver and intestine following exposure to the PXR ligands dexamethasone and L742694 but that MDR1 was only increased in the intestine (Hartley et al, 2004); this most probably reflects the relative importance of metabolism and transport in chemical handling within the liver and intestine. The data presented herein is consistent with such a tissue-specific induction profile, and this may be important given that oral exposure is likely to be the most common route of non-occupational PCB exposure.…”
mentioning
confidence: 97%
“…Previous reports have indicated that another nuclear receptor, pregnane X receptor (PXR), also regulates the expression of UGT2B in the liver. 38,39) In HepG2 human hepatocellular carcinoma cells, the addition of a ligand of PXR, aflatoxin B1, nearly doubled the mRNA expression level of UGT2B7, which is involved in morphine metabolism in humans, and nearly doubled the mRNA expression level of CYP3A4, a target gene of PXR. PXR shows the highest expression in the liver, with some expression also observed in the small and large intestines.…”
mentioning
confidence: 99%